(untitled) (Bangladesh Journal of Pharmacology, 2016)
The objective of the present study was to evaluate the anti-cancer effects of taraxerone in non-small cell lung cancer cells (A-549). The effect of this compound on apoptosis and cellular morphology was also studied. MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) assay was used to evaluate the effect of the compound on cell viability. Cellular morphology after taraxerone treatment was demonstrated by fluorescence microscopy and transmission electron microscopy. The results revealed that taraxerone induced dose-dependent as well as time-dependent growth inhibitory effects on A-549 cell line showing an IC50 value of 53.2 and 61.6 µM at 24 hours and 48 hours time intervals respectively. It also inhibited cancer cell colony formation in a dose-dependent manner and around 90% of the cancer cells were destroyed by the 125 µM dose of taraxerone treatment. Taraxerone also induced cell shrinkage, chromatin condensation and nuclear membrane rupture which are characteristic of apoptosis.